A Study of Mathematical Problems as Control Agents in the Industrial Sector (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
PD Utama Jaya Plasindo, a company specializing in plastic pellet processing, faces several production challenges, such as fluctuating demand, raw material shortages, machinery downtime, and labor management. To address these issues and improve production planning, the company uses MATLAB's linprog tool, which is designed for Linear Programming (LP) and aims to maximize profits. The company's profit is calculated using the formula: Profit = 37A + 46B + 38C + 46D. This calculation takes into account seven constraints related to raw materials, machinery usage, labor hours, and product demand. With this method, PD Utama Jaya Plasindo earns a daily profit of Rp. 837,600 from its plastic buckle products, totaling Rp. 16,752,000 over 20 working days in a month. These profit figures, based on clear objectives and constraints, help ensure that production goals are met and facilitate the monitoring and optimization of production capacity. By leveraging MATLAB's linprog, the company can better manage demand fluctuations and optimize the use of raw materials, machinery, and labor.